Antimicrobial properties and biotransforming ability of fungal endophytes from Ficus carica L. (Moraceae) - Barolo, Melisa Isabel (2023)
The endophytic fungal community associated with leaves of Ficus carica L. (Moraceae) from Argentina was investigated. Fifteen fungal isolates were isolated and identified by molecular methods into the genera Alternaria, Cladosporium, Curvularia, Diaporthe, Epicoccum, Myrothecium, Neofusicoccum, Nigrospora, Preussia and Ustilago. Cladosporium cladosporioides and Curvularia lunata were the most frequently isolated species. The fungal metabolic profiles were obtained by automated TLC and NMR and analysed by PC Analysis. Antifungal and antibacterial activity was assessed by bioautographic assays. In addition, the biotransforming ability of the fungal isolates was tested on F. carica extracts. Five isolates (33.3%) exhibited inhibitory activity against at least one of the microorganisms tested. Most of the fungal endophytes were able to metabolise the flavonoid rutin 1, and the coumarin psoralen 3 present in F. carica extracts. Further investigations of the psoralen biotransforming ability performed by the selected endophyte Alternaria alternata F8 showed the accumulation of the 6,7-furan-hydrocoumaric acid derivative 4 as the main biotransformation product. Our results corroborate that F. carica can live symbiotically with rich and diverse endophytic communities adding insights about their ecological interactions.